Utility evaluation of two molecular methods for Leptospira spp. typing in human serum samples - Landolt, Noelia Yolanda (2023)
Most of the available genotyping methods were applied and evaluated in Leptospira isolates and only few of them in a relevant sample size of blood specimens but not of sera. The objective of this study was to evaluate the utility of one partial 16S rRNA gene sequencing assay (16S rRNA) and an optimized. Multilocus sequence typing scheme (MLST) for Leptospira typing directly in serum samples. Confirmed leptospirosis patients (n = 228) from Argentina (2005–2016) were randomly included. Septicemic-phase serum samples (n = 228) were studied by two genotyping methods. Available immune-phase serum samples of the included patients (n = 159) were studied by MAT to compare serological and molecular results. In culture-proven cases (n = 8), genotyping results between clinical samples and isolates were compared. Typing success rate (TSR) was 21.9% for 16S rRNA and 11.4% for MLST (full allelic profile) and a positive trend in both TSR during the study period was observed. Two species (L. interrogans and L. borgpertesenii) were identified by both methods and MLST assigned 8 different STs. The probable serogroups identified by MLST were coincident with the presumptive infecting serogroups identified by MAT, but with different frequencies. The three serogroups (Canicola, Sejroe and Icterohaemorrhagiae) most frequently identified by MAT were also genotyped by MLST. Typing results via 16S rRNA and MLST in clinical samples and isolates of culture-proven cases, were consistent except for one case. Performance of partial 16S rRNA gene sequencing assay and the optimized MLST scheme directly in sera may increase and improve the knowledge about species and serogroups causing human leptospirosis, especially in countries with low rates of culture sample collection or Leptospira isolation.